Vaginal metastasis of gestational trophoblastic neoplasia resulting in hemorrhage: A case report - Emily Du; Melissa Perez; Tabetha Harken; Jill H. Tseng (Elsevier, 2020)
Complete molar pregnancies complicate approximately 1 in 1500 pregnancies in the United States and result in gestational trophoblastic neoplasia in about 15-20% of these cases. Vaginal metastasis is the second most common site of metastasis and may present with vaginal bleeding and hemorrhage. This report describes a case of a 19-year-old Hispanic primigravida who presented with hemorrhage from an anterior vaginal wall metastasis two weeks after dilation and curettage for complete molar pregnancy. Hemorrhage resolved after extrusion of the lesion from the anterior vaginal wall. Pathology showed markedly atypical trophoblastic tissue from the lesion. Vaginal involvement of gestational trophoblastic neoplasia can present with life-threatening hemorrhage.